Rozwiąż równanie :

a) (x -4)² - 1 = (x - 3)(x-2)
b) (x - 2)² - x (x - 4) = 4(x - 3)
c) (x - 9)(x - 5) = x² + 56 - 14x
d) x² - (x + 3)(x + 4) = x + 20
e) (x - 1)(x + 1) - x(x + 2) - 1 = 2(x + 1)
f) 4(x + 2)² = (2x - 1)(2x + 1) - 2(2x - 1)

Rozwiaz rownania:

a) 3(2x - 1) - 5(x - 3) + 6(3x - 4) = 83
b) 4(x + 2) - 7(2x - 1) + 9(3x - 4) = 30
c) 8(7 - 4y) - 7(4y + 1) + 5(8y - 1) = 19
d) 3(2x + 1) - 5(12x - 7) + 7(6x - 1) = 23
e) 0,2x + 0,5x + 5(5x - 1) - 2,7x = 6,5
f) 0,3(0,4x - 1,2) + 0,36x = 0,6

1

Odpowiedzi

Najlepsza Odpowiedź!
2009-11-19T20:11:13+01:00
A) (x -4)² - 1 = (x - 3)(x-2)
x²-8x+15=x²-5x+6 /-x², -8x,-6
9=3x / :3
x=3
b) (x - 2)² - x (x - 4) = 4(x - 3)
x²-4x+4-x²+4x=4x-12 / +12
16=4x /4
x=4
c) (x - 9)(x - 5) = x² + 56 - 14x
x²-5x-9x+45= x² + 56 - 14x
45=56
rów.sprzeczne
d) x² - (x + 3)(x + 4) = x + 20
x²-x²+4x+3x+12=x+20
7x+12=x+20
6x=8 /:6
x=6/8
e) (x - 1)(x + 1) - x(x + 2) - 1 = 2(x + 1)
x²+x-x-1-x²-2x-1=2x+2
-4=4x /4
-1=x